‘You must carry your wheelchair’ – barriers to accessing healthcare in a South African rural area - Vergunst, Richard (Glob Health Action, 2015)
BACKGROUND: There is international evidence that people with disabilities face barriers when accessing primary healthcare services and that there is inadequate information about effective interventions that work to improve the lives of people with disabilities, especially in low-income and middle-income countries. Poor rural residents generally experience barriers to accessing primary healthcare, and these problems are further exacerbated for people with disabilities. OBJECTIVE: In this study, we explore the challenges faced by people with disabilities in accessing healthcare in Madwaleni, a poor rural Xhosa community in South Africa. DESIGN: Purposive sampling was done with 26 participants, using semi-structured interviews and content analysis to identify major themes. RESULTS: This study showed a number of barriers to healthcare for people with disabilities. These included practical barriers, including geographical and staffing issues, and attitudinal barriers. CONCLUSIONS: It is suggested that although there are practical barriers that need to be addressed, attitudinal barriers could potentially be addressed more easily and cost effectively.